A Comparative Study of Digital Literacy Abilities of Junior High School Students in Urban and Rural Areas - Swasti, Keksi Girindra; Keliat, Budi Anna; Putri, Yossie Susanti Eka; Widyatuti, Widyatuti (Jurnal Kesehatan Vokasional, 2026)
Background: Literacy is important for students as the next generation to contribute to building the future of the nation. Along with technological developments, literacy can be done digitally. Demographic conditions make a difference in the use of digital technology.Objective: This study aims to examine the difference in digital literacy abilities of adolescents based on school location.Methods: This study used a comparative quantitative design with a cross-sectional approach involving 320 respondents of junior high school students aged 12-14 years who were selected using cluster sampling techniques. Adolescent literacy skills are measured using digital literacy instruments. The instrument used has been proven to be valid and reliable. The data was analysed by the Mann-Whitney test.Results: The results of the study showed that there were differences in digital literacy skills between junior high school students in urban and rural schools. Based on the components that make it up, only the ability to choose and obtain information makes a difference.Conclusion: Interventions and policies are needed to improve digital literacy skills in both urban and rural areas.